2013
DOI: 10.1080/10255842.2013.815940
|View full text |Cite
|
Sign up to set email alerts
|

A brain and gaze-controlled wheelchair

Abstract: International audienceno abstrac

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…They also proposed an alternative to deal with difficulties faced by GPS during navigation, such as poor satellite availability, by introducing a fuzzy logic-based algorithm to perform matching wheelchair movements on sidewalks. In our pilot study, 5 a new approach based on combining the user's gaze and his mental activities was introduced in order to assess wheelchair navigation performance in comparison with a standard gaze-based navigation. The results showed that the system performance was better using the combined modalities.…”
Section: Introductionmentioning
confidence: 99%
“…They also proposed an alternative to deal with difficulties faced by GPS during navigation, such as poor satellite availability, by introducing a fuzzy logic-based algorithm to perform matching wheelchair movements on sidewalks. In our pilot study, 5 a new approach based on combining the user's gaze and his mental activities was introduced in order to assess wheelchair navigation performance in comparison with a standard gaze-based navigation. The results showed that the system performance was better using the combined modalities.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the hybrid system could improve performance relative to SSVEP, but it was not the case for P300 BCI. Other efforts matched between brain and other modalities such as muscular activities, 22 or even visual activity 23 and the results concluded are encouraging. However, BCI suffer from some major drawbacks which can influence its acceptability among disabled groups: In fact, due to its emergence, EEG technology did not prove its reliability to fully control a powered wheelchair especially that the number of commands which could be distinguished is very limited.…”
Section: Introductionmentioning
confidence: 78%
“…This fact is also justified by the simultaneous use of gaze and SSVEP: Eyes movements are very rapid and can provide a very reactive system with satisfying execution time but biased performance. 23 The use of SSVEP to validate the selected command increases the performance at the expense of the rapidity. This trade-off is very important because in wheelchair navigation context security is granted with the highest priority.…”
Section: Systems Performances Comparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…The SNP system recognizes four different commands, hard sip, soft sip, hard puff, and soft puff. In [13, 14], the patient controls the wheelchair by tracking the eyes for blinks and estimating gaze direction through a camera placed in front of the wheelchair users. A different and newer ideal is the Tongue Drive System (TDS) developed by a team at Georgia Tech [15].…”
Section: Introductionmentioning
confidence: 99%